1998
DOI: 10.1016/s0029-7844(98)00120-3
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Assessment of Endocervical Canal Length Between 15 and 24 Weeks' Gestation in Women at Risk for Pregnancy Loss or Preterm Birth

Abstract: Weekly rates of endocervical canal length shortening were established, which may be useful for detecting and managing cervical incompetence in high-risk women examined with cervical sonography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
75
1
6

Year Published

2001
2001
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(85 citation statements)
references
References 13 publications
3
75
1
6
Order By: Relevance
“…26,[29][30][31][32][33][34][35][36][37] Many of these studies, however, evaluated low-risk women 29,30,32,34 or those with symptoms of preterm labor. 37 Several studies have evaluated cervical shortening in high-risk women finding conflicting results, with some suggesting it added additional predictive value, 26,31,33 whereas others found it did not.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…26,[29][30][31][32][33][34][35][36][37] Many of these studies, however, evaluated low-risk women 29,30,32,34 or those with symptoms of preterm labor. 37 Several studies have evaluated cervical shortening in high-risk women finding conflicting results, with some suggesting it added additional predictive value, 26,31,33 whereas others found it did not.…”
Section: Discussionmentioning
confidence: 99%
“…26,[29][30][31][32][33][34][35][36][37] Many of these studies, however, evaluated low-risk women 29,30,32,34 or those with symptoms of preterm labor. 37 Several studies have evaluated cervical shortening in high-risk women finding conflicting results, with some suggesting it added additional predictive value, 26,31,33 whereas others found it did not. 35 Shortcomings of previous studies include the fact that many did not evaluate only those identified with a short cervical length, 26,[31][32][33][34] and studies that included only asymptomatic women with singleton gestations found to have a short cervical length did not evaluate other perinatal outcomes apart from preterm birth or gestational age at delivery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Guzman et al 30 established rates of CL shortening from 15 weeks onwards to demonstrate that a rapid change reflects the degree of incompetence. In patients with an incompetent cervix, shortening between 20 and 24 weeks varied from 4.9 to 8 mm, which is the rate between 15 weeks to term in normal pregnancies.…”
Section: Discussionmentioning
confidence: 99%